Novel Aminopyrene Substituted Monospiro/Dispiro Cyclotriphosphazenes: Synthesis, Characterization and Chemosensor Properties - Şenkuytu, Elif (My University, 2018)
In the present work, the novel aminopyrene substituted monospiro/dispirocyclotriphosphazenes (6 and 7) have been synthesized. This compounds were characterized general spectroscopic techniques such as mass, 1H and 31P NMR spectrometry. The photophysical and chemosensor properties toward various metals (Fe3+, Cr3+, Co2+,Al3+, Hg+, Mn2+, Ni2+, Cu2+, Cd2+, Zn2+, Mg2+, Ca2+, Ba2+, Li+, Na+, K+, Cs+) in THF solutionsof aminopyrene substituted compounds were investigated by fluorescence spectroscopy. The metal sensing results showed that compounds 6 and 7 can be candidate fluorescent chemosensors for Cu2+ and Fe3+ ions due to their displaying high selectivity and low limit ofdetection.
Keywords: Kimya; Organik; Kimya; Tıbbi